2015
DOI: 10.5498/wjp.v5.i4.412
|View full text |Cite
|
Sign up to set email alerts
|

Risk for emerging bipolar disorder, variants, and symptoms in children with attention deficit hyperactivity disorder, now grown up

Abstract: World Journal of Psychiatry W J P Retrospective Study ORIGINAL ARTICLEorted significantly higher mean TSC scores: ADHD 3.0; LNCG 1.7; P < 0.001. ADHD status was associated with higher mean NSM: ADHD 2.0 vs LNCG 1.1; P < 0.0001. Also, ADHD subjects had higher PM symptoms than LNCG, with PM means over all time points of 1.3 ADHD; 0.9 LNCG; P = 0.0001. Examining both NSM and PM, ADHD status associated with greater NSM than PM. However, Over 14 years, the NSM symptoms declined and changed to PM over time (df 3, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…However, results from such studies are inconsistent. 2,44,45 For example, the Multimodal Treatment Study did not find that ADHD is associated with increased risk for developing BD but that it is associated with the development of some manic symptoms. 45 In contrast, a recent longitudinal study reported higher incidence rates of BD among individuals with history of ADHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results from such studies are inconsistent. 2,44,45 For example, the Multimodal Treatment Study did not find that ADHD is associated with increased risk for developing BD but that it is associated with the development of some manic symptoms. 45 In contrast, a recent longitudinal study reported higher incidence rates of BD among individuals with history of ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…2,44,45 For example, the Multimodal Treatment Study did not find that ADHD is associated with increased risk for developing BD but that it is associated with the development of some manic symptoms. 45 In contrast, a recent longitudinal study reported higher incidence rates of BD among individuals with history of ADHD. 46 Also, a study of 13,532 twin pairs (9À12 years of age) found that ADHD and hypomanic symptoms were associated with shared genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…11 This situation is further complicated by cumulative maladaptive consequences across a diverse range of outcome areas, including in education, mental health, social dysfunction, vocational underachievement and crime. [23][24][25][26][27][28][29][30] From this group comparison and longitudinal data, it is reasonable to draw a number of conclusions. The first is that underlying biological aetiology probably persists in some form for a significant proportion of children with NB problems.…”
Section: What Research Can Tell Usmentioning
confidence: 94%
“…Multiple studies suggest that clinical challenges persist in many, perhaps the majority, of cases even if the profile of problems changes with time and developmental circumstances . This situation is further complicated by cumulative maladaptive consequences across a diverse range of outcome areas, including in education, mental health, social dysfunction, vocational underachievement and crime …”
Section: What Research Can Tell Usmentioning
confidence: 99%
“…Yet, the task of developing instruments for the assessment of psychiatric conditions in children is challenging because of high comorbidity ( 1 3 ) and significant overlap in clinical features ( 2 ). Our group has a long-standing interest in childhood emotional and cognitive dysregulation and its relevance to the formal diagnostic categories of attention deficit hyperactivity disorder (ADHD) and bipolar disorder (BD) ( 4 7 ). This motivates research into developing instruments for the assessment of childhood behavioral problems that can be easily used in research and clinical care.…”
Section: Introductionmentioning
confidence: 99%